Optimizing Mosque Management Functions with Web-Based Information Technology - Akib, Faisal; Yusuf, Farida (Jurnal INSYPRO (Information System and Processing), 2023)
The large number of mosques in Indonesia and the very varied demographic conditions of society have made it a challenge for the government to set standards for mosque management. In order to actualize the role and function of mosques, it must begin with empowering mosques by carrying out organizational arrangements for the Mosque Prosperity Council (DKM) by empowering all existing potential and making continuous improvements. However, not all DKM have sufficient organizational background. This research aims to develop an information technology system model for assisting DKM with a web-based information technology platform for internal coordination and control of DKM activities themselves. To realize this, the research was carried out using a qualitative field approach using the design and creation method. The results of this research are in the form of an application model that functions as a companion in carrying out DKM tasks. The application is designed to be easy to use even if the user is not completely familiar with technology applications. Keywords: optimizing mosque management; web-based information technology; objective conditions of mosque management